Redes de empresas e seus efeitos sobre o turismo - Flecha, Angela Cabral; Silva, Alcides Volpato Castro e; Fusco, José Paulo Alves [UNESP]; Bernardes, Américo Tristão (Fundação Getúlio Vargas (FGV), Escola de Administração de Empresas de São Paulo, 2012)
O presente artigo tem como objetivo propor um modelo de alinhamento competitivo para a rede de atores do turismo, visando aumentar sua coesão e facilitar a busca de objetivos comuns. Tal proposta foi definida com base na expertise dos autores na análise de redes de turismo, aliada a resultados obtidos na pesquisa em Ouro Preto (MG). Dessa forma, foi possível perceber o peso dos atores envolvidos em função dos critérios de escolha utilizados pelos visitantes para configurar seu caminho dentro da região turística analisada e, assim, reforçar os relacionamentos existentes.

El presente artículo tiene como objetivo proponer un modelo de alineamiento competitivo para la red de actores del turismo, para aumentar su cohesión y facilitar la busca de objetivos comunes. Tal propuesta fue definida con base en la expertise de los autores en el análisis de redes de turismo, aliada a los resultados obtenidos en la investigación en Ouro Preto (MG). de esa manera fue posible percibir el peso de los actores involucrados en función de los criterios de elección utilizados por los visitantes para configurar su camino dentro de la región turística analizada y, así, reforzar las relaciones existentes.

The relationships between firms, to be successful, demand high levels of transparency, information and physical flows of goods and services, in order to provide free access for all people involved in doing business together. The same can be said regarding flow of money resources and talents needed by the processes and operations performed by the network. Thus, the main idea involves reaching balance conditions in terms of sharing the results obtained by all participants, considering their objectives and goals, to keep the network form of organisation as being an adequate strategy. This proposal was defined from the authors' expertise in analysis of tourism networks, together with results obtained on research in Ouro Preto. Thus it was possible to realize the weight of the players involved depending on the selection criteria used by visitors to configure their way into of the tourist region analyzed and thereby strengthen existing relationships.
Redes de empresas y sus efectos sobre el turismo
Business networks and their effects on tourism
Keywords: Redes de empresas; alianças; parcerias; turismo; Ouro Preto; Redes de empresas; alianzas; turismo; Ouro Preto; Networks; alliances; partnerships; tourism sector; Ouro Preto